Making Collaboration Work: A Systematic Multidimensional Review of Collaborative Governance - Setiono, Dede Puji; Kustulasari, Agustina (Jurnal Administrasi Publik (Public Administration Journal), 2025)
Collaborative governance (CG) has become a crucial approach for addressing complex public issues that single actors cannot solve. Despite its growing relevance, the understanding of CG remains fragmented. This study aims to synthesize the existing CG literature to provide a more cohesive understanding and identify a future research agenda. Using a systematic, multidimensional literature review, 53 academic documents were qualitatively analyzed. The findings reveal key antecedent conditions for successful collaboration, including a sense of community, a favorable historical context, and a level playing field. Furthermore, the study identifies eleven critical factors that contribute to effective collaborative networks. The synthesis highlights the strengths of CG literature in institutional and multilevel analysis but also points to significant gaps in integrative dimensions and developmental dynamics. This study contributes a systematic, multidimensional framework that advances collaborative governance theory by integrating institutional, processual, and contextual dimensions and addressing the research gap in comprehensive CG synthesis. The findings reveal that future research must address these gaps to advance both theoretical knowledge and practical application, particularly in diverse contexts like public administration in Indonesia.